Autophagy inhibitor 3-methyladenine mitigates the severity of colitis in aged mice by inhibiting autophagy - Ailing Liu; Hongying Wang; Hong Lv; Hong Yang; Yue Li; Jiaming Qian (Experimental Gerontology)
Background: The elderly ulcerative colitis (UC) patients pose unique challenges due to their comorbidities, diminished functional capacity, and heightened risk of treatment-related complications. Thus, finding a safe and effective treatment for this age group is crucial. Aim: This study investigates the role of autophagy in the pathogenesis of UC in young and elderly patients, and explores the therapeutic potential and mechanisms of autophagy modulators in aged mice with dextran sulfate sodium (DSS)-induced colitis. Methods: Colonic biopsies were collected from young and old UC patients as well as comparable healthy subjects. Young (6–8 weeks) and aged (56 weeks) C57BL/6 mice were treated with DSS to induce acute colitis model. The autophagy inhibitor 3-methyladenine was administered intraperitoneally to aged DSS-induced mice. The autophagy activity was detected by the protein expressions of LC3B-II, p62 and ATG5 by western blot and immunohistochemistry. The levels of TNF -α, IL-6, CCL4, CXCL12 and CD86 were measured by qRT-PCR. The transcriptional activity of NF-κB was measured by electrophoretic mobility shift assay (EMSA). Results: Increased autophagy activity was observed in aged DSS-induced mice. Treatment with 3-methyladenine suppressed autophagy in intestinal epithelial cells (IECs) and alleviated colitis severity. Additionally, 3-methyladenine reduced macrophage recruitment, decreased IL-6 levels, and inhibited NF-κB signaling, thereby mitigating inflammation. Conclusion: Significant differences in autophagy activity were identified between young and aged DSS-induced mice. These findings underscore the potential therapeutic benefits of autophagy inhibition in elderly UC patients.